Brain death, the determination of brain death, and member guidance for brain death accommodation requests: AAN position statement. (29th January 2019) - Russell, James A.; Epstein, Leon G.; Greer, David M.; Kirschen, Matthew; Rubin, Michael A.; Lewis, Ariane
Abstract : The American Academy of Neurology holds the following positions regarding brain death and its determination, and provides the following guidance to its members who encounter resistance to brain death, its determination, or requests for accommodation including continued use of organ support technology despite neurologic determination of death.